Effect of fly ash addition on the fracture toughness of plain concrete at third model of fracture - Golewski, Grzegorz Ludwik (Journal of Civil Engineering and Management, 2017)
A new testing method and estimation of the fracture toughness in Mode III (antiplane shear) of concretes containing: 0, 20 and 30% volume content of the class F fly ash (FA) was proposed. Fracture toughness tests were performed on axial torsional machine MTS 809 Axial/Torsional Test System using special device. The Device for the fracture toughness test at the Mode III fracture consisted of the cylindrical specimen with the formed initial crack, steel plates, and screws with washers securing the specimen in the press holders. The specimens applied for experiments were cylinders with dimensions of 150/300 mm, having an initial circumferential notch made in the half-height of cylinders. The specimens were subjected to pure torsion. The studies examined effect of FA additive on the parameter KIIIc. 20% FA additive causes a small increase of the KIIIc in comparison to the concrete without the FA, while 30% FA additive causes a significant decrease in fracture toughness. The fracture surfaces of the specimens analysed macroscopically were planar. Scanning microscopic observations (SEM) indicate that in the fracture surfaces multilevel cracks occur in the shape of semicircles.